Development of foam concrete with nitrogen oxides removal capability using various forms of titanium dioxide - Jung-Jun Park; Jong-Won Kwark; Kwang Bok Yi; Jong Kyu Kim; Doo-Yeol Yoo (Case Studies in Construction Materials, 2023)
Air quality in Seoul is significantly worse than in major OECD countries, with 1.2–3.5 times higher levels of fine dust and nitrogen dioxide. Photocatalytic reaction with Ca-bound catalyst efficiently removes nitrogen oxides (NOx), especially in building materials, promising solutions for NOx removal in urban air purification. This study therefore investigates the effect of various forms of titanium dioxide (TiO2) on the mechanical properties and NOx removal capability of foam concrete. To produce foam concrete, the type and amount of air foaming agent were optimized. Two types of commercially available TiO2 (P25 and NP600) were incorporated into the foam concrete, alongside synthesized TiO2-mayenite (as an intermixing powder or a coating material). Test results indicated that the incorporation of P25 and NP600 led to increased compressive strength and decreased porosity. The strength increased and porosity decreased, as the amount of TiO2 powders was increased. P25 outperformed NP600 in terms of the NOx removal capacity of foam concrete, with the peak NOx removal capacity (6.07 μmol/50 cm2·5 h) observed at a P25 content of 3%. An even higher NOx removal amount of 6.19 μmol/50 cm2·5 h was achieved by triple-coating the foam concrete surface with 10 wt% TiO2-mayenite. Considering the thickness of the coated TiO2-mayenite and economic feasibility, an approach with dual-coating emerged as the most suitable.